The correlation between full-day school effectiveness and junior high school learners’ character building - Eriswandi (Nalar: Journal of Pedagogy and Society, 2020)
This study aimed to investigate the correlation between full-day school effectiveness and Junior High School learners’ character building in Pekanbaru. The samples were selected from 10% (226) of total 2.226; all junior high school learners in one of region in Pekanbaru city. The data were collected by using questionnaire and were analyzed by applying product moment correlation technique. The results demonstrated that full day school program was implemented very well in Pekanbaru (81-100 with the percentage of 86.7%). In addition, Junior high school learners’ character was also categorized into very good (81-100 with the percentage of 86.7%). Furthermore, it was found out that the very well implemented-full day school program positively correlated with Junior high school learners’ character building in Pekanbaru (0,138< 0,281>0,181 and R Square 0.79 or 7.9%). Moreover, the findings suggested that aside from its negative influence, full day school program influence learners’ character to the extent that it established academic intercommunication system and social relationship. In addition, it avoided learners from brawling against different school learners and performing useless activities. However, it should be emphasized that full day school program provided more benefits to learners.